L’action de groupe, une valeur ajoutée pour l’environnement ? - Maria José Azar-Baud (VertigO)
The adoption of a « group action » in French consumer law leads us to analyze the opportunity of a group action in environmental law and the advantages that may arise from it. Furthermore, two main topics are developed : on the one hand, the type of rights that a group action is intended to protect : the individual homogeneous right which may ensue from an environmental damage and, on the other hand, how this action matches the litigation proceedings already existing in French environmental law. Thus, this paper shows that group actions in environmental law would represent a complementary tool to enhance the effectiveness of environmental rights.